Evaluating the Preventive Measures Vis-a-Vis COVID-19 Pandemic Outbreak Via Siyasah Syar‘Iyyah (Islamic Public Policy) - Mohd Hapiz Mahaiyadin; Zakiah Samori; Roshaimizam Suhaimi; Hisyam Mohd Radzi; Irwan Mohd Subri (AESS Publications, 2024)
International Journal of Asian Social Science, 12(9), 336–346.